(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
These products, unlike wheat, do not contain gluten-forming substances, and therefore are usually used for the production of instant pasta or short instant products or short products using technologies. The use of inulin in functional pasta is natural. Inulin is the most widely used and studied prebiotic in the world, it is a natural plant ingredient.